DEVELOPMENT OF PUSHBROOM AIRBORNE CAMERA SYSTEM USING MULTISPECTRUM LINE SCAN INDUSTRIAL CAMERA - Ahmad Maryanto; Nugroho Widijatmiko; Wismu Sunarmodo; Muhammad Soleh; Rahmat Arief (National Institute of Aeronautics and Space of Indonesia (LAPAN), 2016)
One of the steps on mastery the remote sensing technology (inderaja) for satellite was the development of aerial camera prototype that could be an alternative for LAPAN light cargo aircraft mission (LAPAN Surveillance Aircraft, LSA-01). This system was expected could be operated to fulfill the emptiness or change the remote sensing data of optical satellite as the observer of vegetation covered by cloud. On this research, it was developed a prototype of pushbroom airborne camera 4-channels spectrum with very high resolution that worked on wavelength range seem near infra-red/ NIR used simple components that were available in the commercial market (commercial off-the-shelf/ COTS components). This research also developed georeference imagery software module used method of direct georeference rigorous model that had been applied on SPOT satellite. For this one, it was installed supported sensory for GPS and IMU as the writer of location coordinate and camera behavior while doing the imagery exposure or acquisition. The testing result gave confirmation that COTS components, such as industry camera LQ-200CL, and lower class GPS and IMU could be integrated became a cheaper remote sensing system, which its imagery product could be corrected systematically. The corrected data product showed images with GSD 0.4m still had positioning mistakes on average 157m (400 pixel) from the original position on GoogleEarth. On spectro-radiomatic aspect, the used camera had much higher sensitivity of NIR channel than the looked-channel so it caused bored faster. On the future, this system needed to be fixed by increasing the rate of GPS/ IMU data updates, and increased enough time resolution system so that the synchronization process and the availability supported data for completing more accurate georeference process. Besides, the sensitivity of NIR channel needed to be lower down to make it balance to the looked-channel.